ChemInform Abstract: Single‐Crystal Organic Field‐Effect Transistors of Naphthodifurans. Issue 34 (August 2015) - Mitsui, Chikahiko; Soeda, Junshi; Miwa, Kazumoto; Shoyama, Kazutaka; Ota, Yoshinori; Tsuji, Hayato; Takeya, Jun; Nakamura, Eiichi
Abstract Review: [23 refs.